Zenzo Nkobi, ZAPU Photographer: Exile, Visibility and the Anteroom of War in Zambia, 1977–1980. Issue 5 (2nd September 2020) - Hayes, Patricia
Abstract : Zenzo Nkobi acted as official photographer from 1977 for Joshua Nkomo, president of the Zimbabwe African People's Union (ZAPU). ZAPU was based in Zambia after the banning of the nationalist organisation in Rhodesia in 1963. This article takes up the question of nationalist photography, as it were, and how the modes of documenting presidentialism and pan-African and socialist solidarity in newly independent African states from the 1960s might have shaped Nkobi's influences. Among the photographs taken by Nkobi are pictures of education camps in Zambia during official visits by Nkomo with accompanying foreign delegations. On such occasions, it appears that the youthful camp recruits prepared 'cultural performances' for the visitors. Here, at times, Nkobi's camera goes beyond ostensible political necessity and offers a sense of the contingent and the incidental. The article directs attention to these aspects of the camp photographs and to the spectral implications of the material damage to and digitisation of Nkobi's negatives, which now constitute the photographic heritage of a liberation movement marginalised since independence in 1980.